Flow-induced 2D protein crystallization: characterization of the coupled interfacial and bulk flows. Issue 18 (14th May 2015) - Young, James E.; Posada, David; Lopez, Juan M.; Hirsa, Amir H.
<x xml:space="preserve">Abstract</x> Predictive modeling of biofilm flows, based on first principles, is used to quantify 2D protein crystallization on a ligand-bearing phospholipid film at the air–water interface.